2015
DOI: 10.1007/s00436-015-4655-0
|View full text |Cite
|
Sign up to set email alerts
|

Herd-level prevalence and associated risk factors for Toxoplasma gondii, Neospora caninum, Chlamydia abortus and bovine viral diarrhoea virus in commercial dairy and beef cattle in eastern, northern and northeastern China

Abstract: Although the seroprevalence of Toxoplasma gondii, Neospora caninum, Chlamydia abortus and bovine viral diarrhea virus infection in cattle have been reported in some areas in China, most of them were conducted with small number of cattle samples and very limited districts and neglected the assessment of herd management factors associated with herd-level prevalence of these pathogen infections. Thus, from September 2013 to December 2014, a large-scale seroprevalence study was conducted to determine the animal-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 32 publications
2
19
0
7
Order By: Relevance
“…The risk factors identified in this study, such as the number of cows over two years old, abortion history, and frequent purchase of animals were previously reported (GHALMI et al, 2012;SUN et al, 2015). The main clinical manifestation of cattle infected with N. caninum is abortion (HUSSIEN et al, 2012), which was also observed in this study, because the animals that presented a history of abortion had a 12.8 fold greater risk of infection.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…The risk factors identified in this study, such as the number of cows over two years old, abortion history, and frequent purchase of animals were previously reported (GHALMI et al, 2012;SUN et al, 2015). The main clinical manifestation of cattle infected with N. caninum is abortion (HUSSIEN et al, 2012), which was also observed in this study, because the animals that presented a history of abortion had a 12.8 fold greater risk of infection.…”
Section: Discussionsupporting
confidence: 58%
“…Running water was reported as a possible source of infection for cattle (SUN et al, 2015) because, according to these authors, cattle could consume water contaminated with N. caninum oocysts from feces of infected dogs. Dogs can have access to drinking water and at the same time defecate within or near the water source.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While some typically cause clinical disease, others are underreported because of their often asymptomatic infection in animals (Ayinmode et al 2017, Salifu et al 2019. Exposure of apparently healthy cattle to pathogens of zoonotic and reproductive significance is often detected by serological assays (Sun et al 2015, Ayinmode et al 2017.…”
Section: Introductionmentioning
confidence: 99%